Protective effects of ginsenosides Rg1 and Rb1 against cognitive impairment induced by simulated microgravity in rats - Jiang, Ning; Lv, Jingwei; Zhang, Yiwen; Sun, Xinran; Yao, Caihong; Wang, Qiong; He, Qinghu; Liu, Xinmin (Frontiers in Pharmacology, 2023)
Microgravity experienced during space flight is known to exert several negative effects on the learning ability and memory of astronauts. Few effective strategies are currently available to counteract these effects. Rg1 and Rb1, the major steroidal components of ginseng, have shown potent neuroprotective effects with a high safety profile. The present study aimed to investigate the effects of Rg1 and Rb1 on simulated microgravity‐induced learning and memory dysfunction and its underlying mechanism in the hindlimb suspension (HLS) rat model. Administration of Rg1 (30 and 60 μmol/kg) and Rb1 (30 and 60 μmol/kg) for two weeks resulted in a significant amelioration of impaired spatial and associative learning and memory caused by 4‐week HLS exposure, measured using the Morris water maze and Reward operating conditioning reflex (ROCR) tests, respectively. Furthermore, Rg1 and Rb1 administration alleviated reactive oxygen species production and enhanced antioxidant enzyme activities in the prefrontal cortex (PFC). Rg1 and Rb1 also assisted in the recovery of mitochondrial complex I (NADH dehydrogenase) activities, increased the expression of Mfn2 and decreased the fission marker dynamin‐related protein (Drp)‐1expression. Additionally, Rg1 and Rb1 treatment increased the SYN, and PSD95 protein expressions and decreased the ratio of Bax:Bcl‐2 and reduced the expression of cleaved caspase‐3 and cytochrome C. Besides these, the BDNF‐TrkB/PI3K‐Akt pathway was also activated by Rg1 and Rb1 treatment. Altogether, Rg1 and Rb1 treatment attenuated cognitive deficits induced by HLS, mitigated mitochondrial dysfunction, attenuated oxidative stress, inhibited apoptosis, increased synaptic plasticity, and restored BDNF‐TrkB/PI3K‐Akt signaling.